Organisational culture as a socio-economic phenomenon in the context of the modern management paradigm - Shubin Aleksandr A.; Gladkyy Mykyta O. (Problemi Ekonomiki, 2013)
The article studies cognitive component of the “organisational culture” category and marks our three groups of approaches to the aspect description of the studied category: aspects of the organisational culture formed by the control system; aspects of the organisational culture inherent in the controlled system; and universal aspects inherent in both control and controlled systems. The article provides the authors’ definition of the organisational culture as a complex element of the internal environment of the organisation that has certain phenomenological properties (synergy, dynamics, uniqueness, adaptability, mentality, hierarchy, aggregation, communicativeness and sociality); integrating spiritual, material, static and procedural elements with the aim of formation of a single management philosophy for ensuring external adaptation and efficient functioning of an enterprise. The article establishes the role and place of the organisational culture as a socio-economic phenomenon in the context of the modern management paradigm through specification of prerequisites of formation and development of the neo-classical concept of the organisational culture; features of the modern management paradigm; phenomenological properties of the culture; factors of influence upon the organisational culture and tendencies of development of the phenomenon of the national organisational culture.